Floral Diversity of Loktak Lake, Manipur, India - Devi, Rajkumari Supriya; Lal, Sohan; Maggirwar, Rekha; Jadhao, Ajay B.; Kumar, Sanjeet (Indian Forester, 2025)
A total of 161 plant species were enumerated from Loktak Lake, Manipur, through field surveys carried out in 2017–2019 and 2022–2024. The enumerated species belong to 50 families and 116 genera. It was observed that out of 161, 91 belong to LC (Least Concern), 68 belong to NE (Not Evaluated), and 2 have Data Deficient (DD). The present enumeration will be helpful to restore plant wealth and conservation works.